2015
DOI: 10.1016/s1872-2067(15)60970-6
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-metal-modified ZSM-5 zeolites for improvement of catalytic dehydration of lactic acid to acrylic acid

Abstract: Various ZSM-5 zeolites modified with alkali metals (Li, Na, K, Rb, and Cs) were prepared using ion exchange. The catalysts were used to enhance the catalytic dehydration of lactic acid (LA) to acrylic acid (AA). The effects of cationic species on the structures and surface acid-base distributions of the ZSM-5 zeolites were investigated. The important factors that affect the catalytic performance were also identified. The modified ZSM-5 catalysts were characterized using X-ray diffraction, temperature-programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 25 publications
(19 reference statements)
0
42
0
Order By: Relevance
“…ZSM‐5 (MFI framework) is a medium‐pore zeolite with two intersecting channels that recently attracted a lot of attention by several research groups. Similar to other zeolites, potassium was claimed to be the best counter ion compared to Li, Na, Cs and Rb, independently of the Si/Al ratio used ,,. Furthermore similar to Y and β, low Si/Al ratios seemed beneficial for a high catalytic performance, and a potassium exchange degree (expressed in fraction) of ca.…”
Section: Chemical Routes Of Acrylic Acidmentioning
confidence: 74%
“…ZSM‐5 (MFI framework) is a medium‐pore zeolite with two intersecting channels that recently attracted a lot of attention by several research groups. Similar to other zeolites, potassium was claimed to be the best counter ion compared to Li, Na, Cs and Rb, independently of the Si/Al ratio used ,,. Furthermore similar to Y and β, low Si/Al ratios seemed beneficial for a high catalytic performance, and a potassium exchange degree (expressed in fraction) of ca.…”
Section: Chemical Routes Of Acrylic Acidmentioning
confidence: 74%
“…phosphates [22][23][24][25], rare earth metal phosphates [26][27], hydroxyapatites [28][29][30][31] and various types of alkali and alkaline earth metals modified zeolites [32][33][34][35][36][37]. Majority of these investigations reported that the dehydration of LA efficiently catalyzed over solid acid-base catalysts, which are typically with different acidity strength such as weak acidic and basic sites [26][27][28][29].…”
Section: Scheme 1 Lactic Acid Conversion Routes To Various Reaction P...mentioning
confidence: 99%
“…Another way to modify ZSM-5 zeolites is by using ion exchange with alkali metals [86]. ZSM-5 zeolite (Si/Al molar ratio = 75) was preheated at 550 °C for 6 h and treated with an aqueous solution of MNO 3 (1 mol/L; M = NH 4 , Li, Na, K, Rb, or Cs; 14 g of ZSM-5 zeolite in 140 mL of MNO 3 ) at 80 °C for 6 h to obtain ion-exchanged ZSM-5.…”
Section: State-of-art Of Actual Research Of Obtaining Acrylic Acid Anmentioning
confidence: 99%